PENGARUH TINGKAT PENJUALAN DAN PENCAPAIAN LABA PERUSAHAAN TERHADAP PENDAPATAN KARYAWAN PADA PT. TRACKERINDO ANUGERAH SEJAHTERA - Soesilowati Soema Atmadja (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
This research aims to test the influence between sales levels and profit attainment on employee income. This analysis is a descriptive quantitative that uses independent variables that are the level of sales and profit achievement. The dependent variable is employee income. Data collection was conducted by questionnaire shared with 36 respondents, the sample taken in this study was an employee of PT. Trackerindo Anugerah Sejahtera. In this study used multiple linear analysis methods with testing validity, reliability, classic assumptions and normality. The results of this study show that the level of sales and the achievement of profit affects employee income, the achievement of profit is very influential to the employee's income, but the level of sales does not have a significant effect on the employee's income.